Meta-analysis on the relationship between HLA-DRBl gene polymorphism and cervical cancer in Chinese population. - Lin-Zhen Wei (Public Library of Science (PLoS), 2014)
Aim To determine the association between HLA-DRB1 haplotypes and risk of cervical cancer in unselected and samples from Chinese ethnicities. Methods A comprehensive search for articles from their inception to April 1st, 2013 was conducted from PubMed, Medline, Elsevier Science, Springer Link, Cochrane Library database, China biology medical literature database (CBM),China National Knowledge Infrastructure (CNKI),VIP,and Chinese literature database(Wang fang). A total of 1596 patients with cervical cancer and 2048 controls from the 12 studies on the relationship between gene polymorphism of HLA-DRB l and cervical cancer were performed and data were analyzed and processed using Review Manager 5.0 and Stata 11.0. Results Among the 13 family alleles, two (DRB1*03 and DRB1*08) were found to be negatively associated with cervical cancer in all studies or in Uighur subgroups, and two (DRB1*10 and DRB1*15) were positively associated with in all studies or in Uighur subgroups. Among the 25 specific alleles, six (DRB1*0301, *0403,*0404, *0803, *1312 and *1502) were associated with an increased risk cervical cancer in all studies. No significant association was established for other HLA-DRB1 family alleles and specific alleles. Ethnicity partially explained the race influence of DRB1*12, DRB1*14, DRB1*0301, DRB1*0403, DRB1*0404, DRB1*0803, DRB1*1312 and DRB1*1502 phenotypes. Conclusion Our results support the hypothesis that the HLA-DRB1 family alleles and specific alleles might influence the susceptibility or resistance to cervical cancer, suggesting that immune regulation may play a key role in this disease, although further investigations are still needed.